The management systems of books’ and non-serial publications’ data bases in publishing and book selling - Sakalauskaitė, Edita (Information & Media, 1997)
The article deals with Information Resources Management systems. An analysis of the management systems of books’ and non-serial publications’ databases is discussed; Book Data, Harcourt Brace, McGraw-Hill, their software and hardware requirements, information sources and capacity, and database fields are presented.